JUAL BELI KULIT HEWAN KURBAN MENURUT HUKUM EKONOMI SYARIAH (Studi kasus Masjid At Taqwa, Sumberbulu, Tegalsiwalan, Probolinggo) - Mohammad Arifin; Reza Hilmy Luayyin; Fia Ayuning Pertiwi (LPPM STAI Muhammadiyah Probolinggo, 2023)
Carrying out sacrificial worship by slaughtering sacrificial animals after the implementation of Eid al-Adha and Tasyrik Day prayers is a form of embodiment of our taqwa to Allah SWT and of course with this we are bestowed blessings on the worship. in providing acceptance to the distribution of sacrificial meat, of course, it must be guided by the Qur'an and as Sunnah. The process of slaughtering sacrificial animals carried out by the At Taqwa Mosque, Sumberbulu Village, Tegalsiwalan District, is basically in accordance with the provisions of Islamic law, from the process of receiving sacrificial animals, the slaughter process, the distribution of sacrificial meat to the use of sacrificial animal skins to be worshipped. Buying and selling sacrificial animal skins is in accordance with the provisions of sharia economic law, one of the conditions is that the object of the contract must be valid or not something that is haramed by the Islamic religion. Keywords : Buying and Selling Sacrificial Animal Skins